Customer relationship management practices at Cerebos (Malaysia) Sdn Bhd / Wan Zainorliza Zainal - Zainal, Wan Zainorliza (2009)
Led by its flagship BRAND’S® Essence of Chicken, Cerebos Pacific Limited has empowered the world with it various range of products over 170 years. These milestones mark the start of Cerebos transformation from simply a food company towards a lifestyle business. This transformation requires Cerebos to add on several effort, campaign and strategy for sustainable growth. Those are including invest for growth, rebuilt its process and management infrastructure by adding professionalism and skill sets in several areas especially in Customer Relationship Management (CRM). As a one of big organization, Cerebos (Malaysia) Sdn Bhd enables to gain much other basic benefit through the implementations of Customer Relationship Management such as helping company to identify their target market, manage marketing campaign with clear objectives, providing employees with the information needed and generate quality leads for the sales team. Customer Relationship Management also enables to make company realize that it can maximize the company’s long-term profitability, formation of individualized relationships with the customer, reduce the dependency of the company on trade business and minimizing the tendency of customer to switching cost. It also can help maximize the share of customer’s wallet on the company product and creating unique feeling toward company and product. Lastly, this Customer Relationship Management (CRM) can be one of the company strategy and also a competitive advantage in order to compete with well-establish competitors.